The Utilization of the Montessori Method in Improving the Ability of Clothes Buttoning Up for Student with Physical Impairment - Suryamah, Mamah (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is to explore the utilization of the Montessori method to improve the motor skill of students with physical impairment by practicing buttoning up the clothes using the clothing frame as a media of Montessori. Classroom action research was used as the method in this study. The subject of this study was two eight-year-old elementary students with physical impairment. The result of this study showed the students’ improvement in buttoning up clothes through the media (a clothes frame with 5 buttons on it). The learning result of the second-grade students after interacting with the media through the Montessori method approach showed as 100% and 92.6%. With the score of student activity 100% and 86,6%. For cycle II, the performance test showed 100% and 97. 33%, both students got 100% in student activity test. The highest score of the cycle I was 100% and the lowest score was 86,6%. The highest score of cycle II was 100 and the lowest was 97.33%. Judging from the categorization of learning outcomes, cycle I and cycle II were in the very good category or perfect score. The data obtained indicate that the use of the Montessori approach can improve students' ability to perform buttoning up activities by themselves through using clothes frames with buttons.